Isolation, Characterization, and Antimicrobial Activity of Bacterial and Fungal Representatives Associated With Particulate Matter During Haze and Non-haze Days - Yan, Dong; Zhang, Tao; Bai, Jing-Lin; Su, Jing; Zhao, Li-Li; Wang, Hao; Fang, Xiao-Mei; Zhang, Yu-Qin; Liu, Hong-Yu; Yu, Li-Yan (Frontiers in Microbiology, 2022)
Particulate matter (PM) has been a threat to the environment and public health in a metropolis of developing industrial countries such as Beijing. The microorganisms associated with PM have an impact on human health if they are exposed to the respiratory tract persistently. There are few reports on the microbial resources collected from PM and their antimicrobial activities. In this study, we greatly expanded the diversity of available commensal organisms by collecting 1260 bacterial and 456 fungal isolates from 63 PM samples. Seventy-seven bacterial genera and thirty-five fungal genera were included in our pure cultures, with Bacillus as the most prevalent cultured bacterial genus, Aspergillus, and Penicillium as the most prevalent fungal ones. During heavy-haze days, the numbers of colony-forming units (CFUs) and isolates of bacteria and fungi were decreased. Bacillus, Paenibacillus, and Chaetomium were found to be enriched during haze days, while Kocuria, Microbacterium, and Penicillium were found to be enriched during non-haze days. Antimicrobial activity against common pathogens have been found in forty bacterial and one fungal representatives. The collection of airborne strains will provide a basis to greatly increase our understanding of the relationship between bacteria and fungi associated with PM and human health.